Innovating protectives gears for frontline health professionals in the COVID-19 pandemic at a low resource setting - Adhikari, Rameshwar; Baidya, Suraj; Das, Gaurav; Khatiwada, Lekh Nath; Khatiwada, Shankar Prasad; Lama, Tshering; Chhetri, Ganesh Kunwar; Manandhar, Shrinkhala; Shrestha, Sabina; Subedi, Deepak Prasad; Wagle, Manoj Nidhi (Applied Science and Technology Annals, 2020)
We communicate briefly about the innovation of protective gear (such as Hazmat suit) and respirator mask that can be used by health care professionals as mouth and nose protection tools against the penetration of the microscopic particles containing highly contagious species into the body. As a research and development support to the local entrepreneurs willing to come up with innovative products, the structural and some surface functional properties of the polymeric materials available in local market were analyzed in comparison to the commercially available gears and masks. It has been found that the respirator masks, equivalent in structure and functional properties as the common commercially available protective gears could be developed that can be used by front-line health professionals for protection against contagious environment. The research has paved way to manufacture highly useful health care products at significantly lower costs under low resource setting.